2017
DOI: 10.1152/ajpregu.00268.2016
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and functional characterization of effects of developmental temperature in Drosophila melanogaster

Abstract: The ability of ectotherms to respond to changes in their thermal environment through plastic mechanisms is central to their adaptive capability. However, we still lack knowledge on the physiological and functional responses by which ectotherms acclimate to temperatures during development, and in particular, how physiological stress at extreme temperatures may counteract beneficial acclimation responses at benign temperatures. We exposed Drosophila melanogaster to 10 developmental temperatures covering their en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 69 publications
1
46
1
Order By: Relevance
“…That we should find acclimation in many of our traits is not surprising: acclimation of thermal physiology is commonly observed in a wide diversity of vertebrate and invertebrate terrestrial ectotherms (e.g. Kaufmann & Bennett 1989;Seebacher et al 2015;Schou et al 2017). Consistent with these previous studies, however, the magnitude of change in CT max through acclimation and/or among laboratory-bred individuals is less than for CT min (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…That we should find acclimation in many of our traits is not surprising: acclimation of thermal physiology is commonly observed in a wide diversity of vertebrate and invertebrate terrestrial ectotherms (e.g. Kaufmann & Bennett 1989;Seebacher et al 2015;Schou et al 2017). Consistent with these previous studies, however, the magnitude of change in CT max through acclimation and/or among laboratory-bred individuals is less than for CT min (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, higher CO 2 production in hot-evolved flies is consistent with increasing O 2 consumption associated with decreased AMPK activity (Johnson et al 2010). Further insights into this counter-intuitive pattern of CO 2 consumption comes from a metabolomic analysis of D. melanogaster under a wide range of developmental temperatures (Schou et al 2017). At extreme temperatures the flies were depleted for sugars and energy metabolites (NAD+, NADP+ and AMP), which is attributed to their inability to maintain cellular homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…We chose a linear fit because previous studies have shown that the relationship between CT min and developmental temperature is linear (Schou et al. ), and because linear norm‐of‐reaction analysis is the most commonly used in studies of phenotypic plasticity (Valladares et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…1A). We chose a linear fit because previous studies have shown that the relationship between CT min and developmental temperature is linear (Schou et al 2017b), and because linear norm-of-reaction analysis is the most commonly used in studies of phenotypic plasticity (Valladares et al 2006). The variation of the plastic response (V v.plast ) was computed as the standard error of the regression coefficient ( Fig.…”
Section: Measures Of Environmental Variationmentioning
confidence: 99%